Pre-existing activation states shape functional heterogeneity of human Vγ9Vδ2 T cells - Vyborova, Anna; Gasull-Celades, Laia; Brazda, Peter; Bedate, Alberto Miranda; Karaiskaki, Froso; Sanders, Jasper; Janssen, Anke; Straetemans, Trudy; Beringer, Dennis X.; Sebestyen, Zsolt; Kuball, Jürgen (Frontiers in Immunology, 2026)
γδ T cells gain increasing attention as carriers for tumor-targeting constructs in therapeutic contexts. However, the failure to fully account for the diversity within the subset has impeded its clinical use so far. We investigated the heterogeneity of the Vγ9Vδ2 T-cell compartment by profiling the function and gene expression of single-cell clones expanded in vitro using the rapid expansion protocol (REP), which involves repeated stimulation with interleukin (IL)-2 and IL-15. Generally known to enhance the type 1 effector program in the γδ T cells, these culture conditions polarized only a proportion of the adult peripheral blood-derived clones toward “classic” type 1 effectors marked by high interferon gamma (IFN-γ) release (HIR). Unexpectedly, a substantial fraction of the clones exhibited a low-IFN-γ-releasing (LIR) profile and instead activated a type 2-like effector program, marked by IL-4 and IL-5 secretion and expression of the transcription factor GATA3. In line with this functional dichotomy, we observed coordinated transcriptional programs linking effector function to genes associated with T-cell activation, proliferation, and cytokine production. HIR clones exhibited a more activated transcriptional profile in culture compared with LIR clones. Importantly, projection of HIR and LIR gene signatures onto ex vivo single-cell transcriptomic data demonstrated that these effector states are already present in vivo as part of a continuous activation landscape within nonexpanded Vγ9Vδ2 T cells, with LIR-like states predominating in cord blood and remaining prevalent in adult peripheral blood. These findings indicate that the functional divergence observed after in vitro expansion reflects stabilization and amplification of preexisting activation states rather than culture-induced polarization. Analysis of the Vγ9Vδ2 T-cell receptor repertoire further suggested that intrinsic signaling features may modulate, but do not dictate, effector differentiation within this activation continuum. In summary, our data indicate that effector differentiation of Vγ9Vδ2 T cells is dominated by a preexisting LIR-like activation state, a finding with major implications for current γδ T-cell-based cancer immunotherapy strategies that rely on in vivo stimulation or ex vivo engineering.